Chemical Compositions and Tyrosinase Activity of the Essential Oils of Alpinia aquatica - Nissha, Bharrathi Romes; Norazah, Basar; Hasnah, M. Sirat; Siti Ernieyanti, Hashim; Zaini, Assim (SAGE Publications, 2018)
The essential oils obtained from the fresh rhizome, leaf, and pseudostem of Alpinia aquatica Roscoe. were hydrodistillated and analyzed using capillary gas chromatography (GC) and gas chromatography-mass spectroscopy (GC-MS). β-Pinene (11.7%), α-humulene (8.9%), aromadendrene (8.7%), and sabinene (7.7%) were the major components in the rhizome oil. The most abundant components of the leaf oil were germacrene D (21.3%), β-pinene (15.6%) and sabinene (12.1%), while α-humulene (19.8%), germacrene D (15.2%) and β-caryophyllene (8.7%) were the main constituents in the pseudostem oil. Antityrosinase assay revealed that all the three essential oils exhibited weak tyrosinase inhibition activities. The rhizome oil showed the highest inhibition activity with the value of 9.5% for the L-DOPA oxidation.